Pengaruh Harga Dan Gaya Hidup Terhadap Keputusan Pembelian Iphone Pada Mahasiswa Kedokteran UHN Medan - Silaban, Fitri Suriani Br.; Manalu, Darma; Simangunsong, Ridhon (Research and Community Service UNIVERSITAS KALBIS, 2025)
This study aims to analyze the influence of price and lifestyle on iPhone purchasing decisions among Faculty of Medicine students. iPhone products are known for their premium quality which is a symbol of social status, so they are chosen by many students who prioritize a modern lifestyle. This research used a quantitative method with a survey approach, where data was obtained through questionnaires distributed to 96 students from the Faculty of Medicine. The analysis technique used is multiple linear regression to determine the influence of price and lifestyle on iPhone purchasing decisions. The research results show that these two variables, price in accordance with product quality and lifestyle that supports social status, have a significant influence on purchasing decisions. These findings provide a deeper understanding of the factors that influence premium product purchasing decisions, especially among students.